PELATIHAN PENGENALAN TEKNOLOGI CLOUD COMPUTING UNTUK MENINGKATKAN LITERASI DIGITAL GURU-GURU di SMK JP1 JAKARTA PUSAT - Is Mardianto; M Najih; Binti Solihah (JUARA: Jurnal Wahana Abdimas Sejahtera, 2022)
Cloud computing technology is one of the pillars of Information technology which is the foundation for the Industrial Revolution 4.0. Mastery of this technology is needed by prospective middle-class workers to be easily absorbed by the industry. SMK Jakarta Pusat 1, as a provider of human resources for software engineering skills, needs to update the knowledge and skills of teachers to meet these needs. The PKM team of Informatics Departemen of Universitas Trisakti held a cloud computing workshop to update the knowledge of SMK JP1 teachers. Pre-test and post-test were used to measure the knowledge level of participants. The training materials include various cloud computing services, the utilization of IaaS services, and the installation of e-commerce web applications on Digital Ocean's cloud services. The post-test results showed that the workshop participants could participate well in training. As many as 67% of the training participants gave a positive impression of this activity and expected more intensive training and a longer duration of time. The output of this training in the form of a training module is very relevant and can enrich the Cloud computing practice course at the Trisakti Informatics Engineering Department